(untitled) (Interdisciplinary Studies Journal, 2025)
This article explores the interrelationships between the creative economy, sustainability and social impact, highlighting how these three pillars can work together to promote economic and social development. Through a qualitative narrative review of recent literature, the study discusses how the creative economy, characterized by innovation and the appreciation of cultural diversity, has consolidated itself as an important economic driver in several parts of the world, including Brazil, where sectors such as fashion, design, audiovisual and visual arts play a crucial role in job creation and economic growth. However, in addition to its capacity to generate wealth, the article also addresses the transformative role of the creative economy in strengthening social cohesion and the inclusion of marginalized communities, promoting the appreciation of cultural identities and offering new opportunities for local development. The social impact of the creative economy is discussed as an effective tool for social inclusion and the empowerment of marginalized communities, highlighting cultural projects and solidarity economy initiatives that have generated significant social transformations in contexts of vulnerability. Through an integrated analysis, the article suggests that the creative economy, when associated with sustainable practices and effective public policies, can act as a powerful vector for sustainable development and social transformation, pointing to the need for more investment and more inclusive governance to expand its positive effects in the future.